The North-South divide: Sources of divergence, policies for convergence - Lucrezia Fanti; Marcelo C. Pereira; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2022)
Building upon the labour-augmented K+S modelling framework (Dosi et al., 2010, 2017, 2020), we address the analysis of the North-South divide by means of an agent-based model (ABM) endogenously reproducing divergence between two artificial macro-regions characterized by identical initial conditions in terms of productive and innovation structures, but different labour market organizations. Given the ex-ante initial conditions, we identify the role played by different functioning of the labour markets on the possible divergence across the two regions. We do find that divergences in labour market reverberate into asymmetric productive performance due to negative reinforcing feedback loop dynamics. We then confront alternative policy schemes by showing that investment policies directed at increasing machine renewal and higher substitutionary investment are the most effective in fostering the convergence process.
Keywords: C63; J3; E24; O1; 330; Agent-Based Models; Technology Gap; Labour Market